Ibn-e-Batuta Say Ibn-e-Insha Tak : Shahkaar Safarnamon Aur Ripotaz Say Intakhab - Edited by Iqrar Hussain Sheikh (Lahore K. K & Sons, 2000)
Shahkaar Safarnamon Aur Ripotaz Say Intakhab.
Include Bibliography.
Urdu Travelogue.
Keywords: Literature - Travelogue -- Literature - Urdu Travelogue -- Urdu Literature - Travelogue